PATHOPHYSIOLOGICAL RATIONALE FOR THE USE OF A NEW AMINO ACID MIXTURE FOR LIVER DAMAGE - Sayfutdinova Z. A., Xashimova G. Y., Yusupov B. N., Muhammadiev X. G., Shomansurova G. E. (Galaxy International Interdisciplinary Research Journal, 2023)
Objective: determination of the pathophysiological validity of the use of the new amino acid mixture for damage to the liver.Materials methods. Acute heliotrin intoxication is reproduced by single administration of rats subcutaneous sub-lethal doses of heliotrin, prepared at the rate of 40 mg per 100 g of body weight. Toxic hepatitis is reproduced by subcutaneous administration of heliotrin. Results. During the reproduction of experimental toxic hepatitis by introducing heliotrin, it was found that the HIF-1 content was on average 0.101667 ± 0.0022 ng /l. In blood plasma, the average HIF-1 was 0.2136 ± 0.0066 ng / L. Such indicators are explained by the effect of heliotrin on the liver and, above all, on hepatocytes, in which mitochondria are experiencing an oxygen deficiency. Thus, HIF-1 acts as an early biomarker of oxygen tissue deficiency and since it causes angiogenesis, the strengthening of this gene in experimental animals with ischemia can contribute to the proliferation of vessels necessary for oxygenation. Conclusions: The developed aminoacid mixture in terms of the effectiveness of the impact on the development and course of experimental toxic hepatitis surpasses traditional methods of treatment, which is proved by the study.